Control Method of Microgrid Grid Connected Inverter Based on Quantum GA-PID - Yunqing Qu (EAI Endorsed Transactions on Energy Web, 2025)
The current trend is towards ever-increasingly rigorous control performance requirements for grid-connected inverters. Therefore, a proportional integral derivative control method of the quantum genetic algorithm and particle swarm optimization has been proposed, which can achieve stable and efficient operation of microgrids.The total harmonic distortion of the improved controller was 1.03%, which was 1.98% lower than the traditional method and far below the national standard of 5%; The prediction accuracy wad on average 82%, 51%, and 54% higher than the other three classic algorithms; After the improvement of sag, the smoothness of microgrid switching had been increased, avoiding severe shaking. The convergence time was 68.3%, 54.5%, and 35.5% shorter, and the average convergence algebra was improved by 60.1%, 67.2%, and 87.3%, respectively; The control step response only approached 1.5 after 0.4 seconds, which was 75% longer than the improved time, and the overshoot was 0. Accordingly, the proposed method is able to utilizefor the regulation of actual microgrid grid-connected inverters, achieving effective voltage control in dynamic and complex environments.